2019
DOI: 10.1159/000498853
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Head-Out Aquatic Exercise on Arterial Stiffness in Middle-Aged and Elderly People

Abstract: Aquatic exercise is ideal for older adults because it mitigates weight-bearing stress. However, the effect of head-out aquatic exercise on arterial stiffness, a strong future cardiovascular disease (CVD) risk, remains unclear. We determined whether head-out aquatic exercise would mitigate arterial stiffness in middle-aged and elderly people. In 25 middle-aged and older people (9 men, mean age 64 ± 8 years), blood pressure (BP) and brachial-ankle pulse wave velocity (baPWV) were measured before and after a supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Several intervention studies demonstrated that swimming exercise training improved arterial stiffness and aortic hemodynamics ( 8 12 ). On the other hand, we ( 13 ) and others ( 14 , 15 ) showed head-out aquatic exercise training-induced favorable reduction in arterial stiffness, while the influence on aortic hemodynamics remained fully unknown.…”
Section: Introductionmentioning
confidence: 82%
“…Several intervention studies demonstrated that swimming exercise training improved arterial stiffness and aortic hemodynamics ( 8 12 ). On the other hand, we ( 13 ) and others ( 14 , 15 ) showed head-out aquatic exercise training-induced favorable reduction in arterial stiffness, while the influence on aortic hemodynamics remained fully unknown.…”
Section: Introductionmentioning
confidence: 82%
“…Several intervention studies demonstrated that swimming exercise training improved arterial stiffness and aortic hemodynamics (8)(9)(10)(11)(12). On the other hand, we (13) and others (14,15) showed head-out aquatic exercise training-induced favorable reduction in arterial stiffness, while the influence on aortic hemodynamics remained fully unknown.…”
Section: Introductionmentioning
confidence: 66%